The effects of ethosuximide on amino acids in genetic absence epilepsy rat model - (:unkn) unknown (JAPANESE PHARMACOLOGICAL SOC, 2006)
Genetic absence epilepsy rats from Strasbourg (GAERS), a selectively inbred strain of Wistar rats, has been validated as an experimental model for human absence epilepsy. In this model, systemic administration of ethosuximide (ETX) was shown to reduce the spike and wave discharges (SWD). In this study, gamma-aminobutyric acid (GABA) and L-glutamic acid levels in response to ETX injections (i.p., 100 mg/kg) were measured in the microdialysis samples collected from the ventrolateral thalamus (VLT) and the primary motor cortex (M I) area of Wistar rats and GAERS by using HPLC with fluorescent detection. Throughout the microdialysis procedure, continuous EEG recording was performed where ETX was shown to suppress the SWD activity. We demonstrated increased basal GABA levels in the M1 and VLT of GAERS, and ETX treatment did not produce any effect on higher GABA levels in the VLT, but suppressed the increased GABA levels significantly in the M I of GAERS. All these findings denote the importance of corticothalamic circuitry and the role of increased GABA tonus in primary motor cortex and thalamus of GAERS. The primary motor cortex also seems to be involved in the SWD activity and ETX exerts, at least partially, its neurotransmitter effects through it.
Keywords: gamma-aminobutyric acid; L-glutamic acid; primary motor cortex; thalamus; absence epilepsy; WAVE DISCHARGES; EXTRACELLULAR GABA; SEIZURES; THALAMUS; SPIKE; CORTEX